ISSLS prize winner: Lumbar vertebral endplate lesions: associations with disc degeneration and back pain history - Wang, Yue; Videman, Tapio; Battié, Michele C (Spine (Philadelphia, Pa. 1976), 2012)
An autopsy study. To investigate associations between various types of lumbar endplate lesions, disc degeneration (DD), and back pain history. The well-innervated vertebral endplate has been suspected as a source of back pain. Previously, we observed 4 types of lumbar endplate lesions with distinct morphological characteristics. Their roles in DD and back pain remain unclear. From a lumbar spine archive of 136 men (mean age, 52 yr), back pain, back injury, and occupation history data for 69 subjects and discography data for 443 discs from 109 subjects were available for study. Back pain history was categorized as none, occasional, or frequent. DD was judged from discography. Endplate lesions were classified as Schmorl's nodes, fracture, erosion, or calcification, and lesion size was rated as none, small, moderate, or large. Associations between endplate lesions and DD, back pain history, back injury, and occupation history were examined. Presence of endplate lesions was associated with frequent (odds ratio [OR] = 2.57) but not occasional back pain. However, large endplate lesions were associated with both occasional (OR = 8.68) and frequent (OR = 17.88) back pain. This association remained after further controlling for DD. Also, the presence of each type of endplate lesion was associated with adjacent DD (OR = 2.40-9.71), with larger lesions associated with more severe DD. Endplate erosion lesions were more strongly associated with adjacent DD than Schmorl's nodes. Although back injury history was associated with the presence of fracture and erosion lesions, heavy occupation was associated with the presence of Schmorl's nodes. Endplate lesions are associated with back pain as well as being closely associated with adjacent DD, with a clear dosage effect. Different types of endplate lesions seem to have different magnitudes of associations with DD. Lumbar endplate lesions may be an important key to better understand both DD and back pain.